2011 2nd International Conference on Advancements in Nuclear Instrumentation, Measurement Methods and Their Applications 2011
DOI: 10.1109/animma.2011.6172964
|View full text |Cite
|
Sign up to set email alerts
|

Intracavitary in vivo dosimetry based on multichannel fiber-coupled Radioluminescence and Optically Stimulated Luminescence of Al<inf>2</inf>O<inf>3</inf>:C

Abstract: Real-time dose measurements may also be performed by recording the RadioLuminescence (RL), spontaneously emitted by the crystals during irradiation. In this case, a correction method is implemented to correct for stem effect influence (Cerenkov and scintillation generated within the fibers). For BT, the dual-fiber subtraction method is used (using a reference fiber) whereas the time discrimination method is used for IMRT. The experimental dose distribution leads to an underestimation of the source-sensor dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…For the sake of demonstration, only one sensor was used but this measurement protocol may be extended to a plurality of sensors (e.g. a dosimetric catheter including a chain of Al2O3:C crystals for intracavitary IVD [20]), connected to a multichannel RL-OSL/FO reader.…”
Section: Discussionmentioning
confidence: 99%
“…For the sake of demonstration, only one sensor was used but this measurement protocol may be extended to a plurality of sensors (e.g. a dosimetric catheter including a chain of Al2O3:C crystals for intracavitary IVD [20]), connected to a multichannel RL-OSL/FO reader.…”
Section: Discussionmentioning
confidence: 99%
“…The second generation (OSL2) relies on alumina crystals. We have shown that the dose resolution is well < 50 µGy [13], enabling for instance, an average dose rate measurement as low as 50 µGy/h with 1 h integration [12]. The OSL2 system is a CW multichannel unit (16 outputs) built in a 19" enclosure including a diode-pumped solid-state laser (532 nm), and a 16-channel fibre switch.…”
Section: Dosimetry Based On Fiber Remote Optically Stimulated Lumines...mentioning
confidence: 99%
“…The OSL2 system is a CW multichannel unit (16 outputs) built in a 19" enclosure including a diode-pumped solid-state laser (532 nm), and a 16-channel fibre switch. It is linked by USB to a laptop running with a dedicated LabView  software [13]. It includes PMMA fibers and tiny alumina crystals (0.3 x 0.3 x 1 mm 3 ) inserted into fiber tips.…”
Section: Dosimetry Based On Fiber Remote Optically Stimulated Lumines...mentioning
confidence: 99%
“…The fiber collects the light emitted by the scintillator during irradiation (radioluminescence, RL) and a light detector placed at the other extreme of the optical fiber measures its intensity. In other words, FOD technique allows for in-vivo and real-time dose assessment, and since its small size not only permits accurate measurements in regions of high dose gradients but intracavitary measurements can also be performed (Spasic et al, 2011).…”
Section: Introductionmentioning
confidence: 99%